2017
DOI: 10.1016/j.jvscit.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A rare anatomic variant of a single-conduit supraclavicular cephalic arch draining into the external jugular vein presenting with recurrent arteriovenous fistula stenosis in a hemodialysis patient

Abstract: The cephalic arch is a common location of stenosis, especially in brachiocephalic fistulas. The cephalic arch has a number of anatomic variations. Cephalic arch stenoses are often resistant and have poor primary patency. Here we describe an unusual case of a hemodialysis patient with a single-conduit supraclavicular cephalic arch draining into the external jugular vein presenting with recurrent cephalic arch stenoses and external jugular vein stenosis. In our view, extrinsic compression by the clavicle may con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Esta variación tiene una frecuencia del 0,7 % al 5,4 % en la bibliografía consultada. Corresponde al remanente embriológico denominado vena yugulocefálica persistente (VYC), típica de primates no humanos, y reportada de manera esporádica en humanos (Jun et al, 2017;Latarjet & Ruiz Liard;Maalman et al;Novakov & Krasteva;Russo et al) Así mismo, la literatura describe casos en los que el AVC puede drenar también en la vena yugular interna (VYI) o directamente en la vena subclavia (VS), siendo esta última, la variación más frecuente (Kiev & Asif; Lau et al).…”
Section: Discussionunclassified
“…Esta variación tiene una frecuencia del 0,7 % al 5,4 % en la bibliografía consultada. Corresponde al remanente embriológico denominado vena yugulocefálica persistente (VYC), típica de primates no humanos, y reportada de manera esporádica en humanos (Jun et al, 2017;Latarjet & Ruiz Liard;Maalman et al;Novakov & Krasteva;Russo et al) Así mismo, la literatura describe casos en los que el AVC puede drenar también en la vena yugular interna (VYI) o directamente en la vena subclavia (VS), siendo esta última, la variación más frecuente (Kiev & Asif; Lau et al).…”
Section: Discussionunclassified
“…The cephalic vein (CV) passes between the deltoid and pectoralis major muscles (deltopectoral groove) and through the deltopectoral triangle, where it empties into the axillary vein and continues to the subclavian vein under the clavicle. CV has recently been used in invasive clinical procedures such as cardiovascular implantable electronic device implantation [5,7,12,15,28] and catheterisation [17], since it is remarkably constant superficial structure in the upper arm and axilla [34], has large size enough to facilitate easy cannulation [3,16,17], and known to have lower risk of injury to neighbouring structures than axillary vein puncture [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, some anatomic variants exist and include the bifid and trifid arch (4). Jun et al reported a rare anatomic variant of a single-conduit supraclavicular cephalic arch draining directly into the external jugular vein, and this case involved recurrent stenosis of the cephalic arch and external jugular vein (6). We suppose that idiopathic CAS combined with congenital cephalic arch anomalies can induce rare retrograde venous reflux into the ipsilateral external jugular vein and can subsequently lead to SOV enlargement, as observed in our case.…”
mentioning
confidence: 99%